SCOPE OF EDUCATIONAL FINANCING MANAGEMENT AS A STRATEGY TO DEVELOP QUALITY ISLAMIC EDUCATIONAL INSTITUTIONS - Jailani, Abdul Bari (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Educational financing is a central system in education. The use of financing to support the targeted improvement of educational quality must be understood through the implementation of educational financing management systems. This includes the concept of educational budgeting, the classification of activities, the determination of standards, and the calculation of unit costs in educational budgeting.Educational financing management consists of three important stages: planning, implementation, and evaluation. When applied to financial management, these stages become the budgeting phase, the accounting phase, and the auditing phase.A well-implemented educational financing management system is expected to support and ensure the development of the quality and standards of education, as well as the smooth running of teaching and learning activities.